(untitled) (Journal of Advances and Scholarly Researches in Allied Education, 2022)
C.amada an explorable member ofZingiberaceae family for its medicinal importance. It showsresembles to turmeric . C. amadacommonly known as mango ginger, because of its raw mango taste andappearance that of ginger. They are used in making pickles in Dakshin Bharat and used as spice in makingof household food. It constitutes carbohydrate, terpenes, curcuminoids, volatile essential oils, phenolicacids. In Ayurveda, it is termed as Amma haridra or KarpuraHaridra. Like other Curcuma spp., C.amadaalso has many therapeutic properties. Especially useful in digestive complaints, give relief inabdominal gas, promotes appetite and improves digestive strengths. Moreover C. amada also possessescancer preventive properties, anti aging, antioxidant activity. The proper management of theseunderused rhizomes in their original habitat will improve the biodiversity enrichment of these rhizomesand consumption of it minimizes the degenerative diseases. This review summarizes the importance ofC. amada in today’s burning issues.